Small for gestational age: A risk factor for the development of hypertension in childhood? - SURPURE, SHREYAS; SHARMA, SHOBHA; SASTE, SONAL; KABRA, NANDKISHOR; BAVDEKAR, SANDEEP (Indian Journal of Child Health, 2022)
Background: There is conflicting evidence regarding the association of elevated blood pressure and SGA status. Most of the studies showing positive association have demonstrated this association in children aged above 7 years. Objectives: To determine if there is a significant difference between the proportion of children aged 3-5 years, born-SGA and those born-AGA developing hypertension. Methodology: The observational cross-sectional study was carried out at a private tertiary care hospital. Clinically healthy children (age: 3-5 years) were enrolled and grouped as those who born-SGA and those who were born AGA. Blood pressure was recorded with oscillometric device and procedure was repeated three times at an interval of at least 10 minutes. The mean of three blood pressure recordings was considered as the participant’s true blood pressure. The demographic characteristics of the study population were summarized using descriptive statistics. Categorical outcomes were compared by using Chi square or Fischer exact test. For continuous outcomes, ‘t test’ was used. P value of less than 0.05 was considered statistically significant. Results: The study enrolled 27 SGA-born children and 27 AGA-born children. Nine children (33.33%) in the SGA group and one child (3.7%) in the AGA group developed hypertension (p= 0.011). The systolic blood pressure in the SGA group (103.20±8.62 mmHg) was significantly higher than that in the AGA group (98.58±6.60 mmHg) (p=0.031). The diastolic blood pressure (mean ± SD) in the SGA group was 62.75 ± 9.19 mm Hg. There was no significant difference between the diastolic blood pressures in the two groups (AGA: 59.00±5.11mm Hg, SGA: 62.75 ± 9.19; p= 0.07). Conclusion: Being born SGA was thus found to be a risk factor for hypertension in 3-5 years old children.